Continuous exposure of pancreatic cancer cells to dietary bioactive agents does not induce drug resistance unlike chemotherapy - Fan, Pei; Zhang, Yiyao; Liu, Li; Zhao, Zhefu; Yin, Yefeng; Xiao, Xi; Bauer, Nathalie; Gladkich, Jury; Mattern, Johannes; Gao, Chao; Schemmer, Peter; Gross, Wolfgang; et al. (Cell death & disease, 2016)
The repeated treatment of cancer cells with chemo- or radiotherapy induces therapy resistance, but it was previously unknown whether the same effect occurs upon continuous exposure of cancer cells to diet-derived chemopreventive agents. We elucidated this interesting question in pancreatic ductal adenocarcinoma, which is a highly aggressive cancer entity with a marked resistance toward gemcitabine and other cytotoxic drugs. The isothiocyanate sulforaphane, present in cruciferous vegetables, and the polyphenol quercetin, present in many fruits and vegetables induced apoptosis and reduced viability in gemcitabine-sensitive BxPC-3 cells but not in non-malignant ductal pancreas cells and mesenchymal stromal cells. In turn, BxPC-3 cells were treated with increasing concentrations of gemcitabine, sulforaphane or quercetin for more than 1 year and the surviving subclones Bx-GEM, Bx-SF and Bx-Q were selected, respectively. While Bx-GEM cells acquired a total resistance, Bx-SF or Bx-Q cells largely kept their sensitivity as proved by MTT assay, annexin staining and FACS analysis. The evaluation of the self-renewal-, differentiation- and migration-potential by colony formation, differentiation or migration assays demonstrated that cancer stem cell features were enriched in gemcitabine-resistant cells, but decreased in sulforaphane- and quercetin-long time-treated cells. These results were confirmed by orthotopic xenotransplantation of cancer cells to the mouse pancreas, where Bx-GEM formed large, Bx-Q small and Bx-SF cells almost undetectable tumors. An mRNA expression profiling array and subsequent gene set enrichment analysis and qRT-PCR confirmed that tumor progression markers were enriched in Bx-GEM, but reduced in Bx-SF and Bx-Q cells. This study demonstrates that the continuous exposure of pancreatic cancer cells to sulforaphane or quercetin does not induce resistance in surviving cells but reduces tumorigenicity by inhibition of tumor progression markers. These results highlight that cancer cells may not adapt to the preventive and therapeutic effects of a regular fruit- and vegetable-based diet.
Gesehen am 18.06.2020